The Scream: Lament as a Way to Hear Silence Into Speech - Cooke, Amanda (Pastoral psychology, 2024)
In this article, I discuss Edvard Munch’s iconic artwork, The Scream, as a contemplation on the voicelessness of intense suffering and the power of lament. I first recall a clinical case in the hospital setting where a patient was lamenting but lacked compassionate witnesses to understand her lament. I then discuss Munch’s iterative process for creating The Scream and explore questions that this masterpiece evokes. Painted in 1893, the work resonates with its viewers, powerfully representing human anguish, anxiety, and existential dread. I review Munch’s biography and upbringing, suggesting that Munch’s painting is his own attempt at having the viewer witness his own lament—a witness he did not have in his childhood. After reflecting on The Scream and Munch’s upbringing, I discuss theologian John Swinton’s work on lament. He asserts that lament is a faithful response to suffering and can restore the sufferer’s faith and relationship with God. I assert that a similar framework, such as asking patients to speak their own illness narrative, should be further explored as an important part of modern holistic medical care.